Contribution of the TRPM4 Channel to Osteogenic Differentiation of Human Aortic Valve Interstitial Cells - Margaux Aize; Arthur Boilève; Benoit D. Roussel; Laura Brard; Harlyne Mpweme Bangando; Corentin Kerevel; Alexandre Lebrun; Hind Messaoudi; Vladimir Saplacan; Alain Manrique; Romain Guinamard; Christophe Simard (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Aortic stenosis due to deleterious remodeling of the aortic valve is a health concern since it can be corrected only by valve replacement due to the poor knowledge of cellular mechanisms involved. Fibroblastic valvular interstitial cells (VICs) play a central role in valve leaflet stiffness by trans‐differentiation into osteoblast‐like cells leading to calcification. The TRPM4 (transient receptor potential melastatin 4) cation channel was shown to participate in cardiac fibroblast remodeling. It is also involved in radiation‐induced aortic valve remodeling in vivo in mice. We hypothesized that TRPM4 might participate in human VIC transition to osteoblastic phenotype. Methods Human aortic valves were collected from patients undergoing surgical valve replacement. Isolated VICs were maintained 14 days in culture in standard or pro‐calcifying media and submitted to the TRPM4 inhibitor 9‐phenanthrol, or small hairpin RNA–TRPM4. Osteogenic differentiation was evaluated by measuring hydroxyapatite crystals by Alizarin red staining and protein expression of osteogenic markers. Results Western blot on VICs revealed TRPM4 protein expression and channel functionality was confirmed by patch‐clamp recordings exhibiting a cationic current sensitive to voltage and internal Ca2+. VICs maintained in pro‐calcifying media exhibited a higher mineralization than in standard media, with an increase in osteogenic markers. Mineralization and osteogenic markers (bone morphogenetic protein 2, runt‐related transcription factor 2) were decreased when pro‐calcifying media contained 9‐phenanthrol or small hairpin RNA–TRPM4. Similarly, SMAD1/5 and nuclear factor of activated T‐cell pathways were stimulated in pro‐calcifying media conditions compared with standard media but reduced by 9‐phenanthrol or small hairpin RNA–TRPM4. Conclusions TRPM4 participates in osteogenic differentiation of human VICs and thus appears as a target to prevent aortic valve remodeling.